Chiral tandem modifiers: highly efficient cinchonidine-derivative modifiers at low concentrations for the enantioselective hydrogenation of (E)-2, 3-diphenylpropenoic acid over Pd/C. Issue 23 (24th October 2022) - Mameda, Takuya; Shimogaki, Mio; Okamoto, Yasuaki; Sugimura, Takashi
Abstract : Chiral tandem modifiers linking two or three cinchonidine molecules at the 2′-position of the quinoline ring are highly effective at low concentrations for the enantioselective hydrogenation of PCA over Pd/C. Abstract : A novel group of chiral modifiers is successfully developed to achieve high enantioselectivity in the asymmetric hydrogenation of ( E )-2, 3-diphenylpropenoic acid (PCA) over Pd/C at a low modifier concentration. It is found that the tandem modifiers synthesized by linking two or three cinchonidine (CD) molecules with alkyl or aromatic linkers at the 2′-position of the quinoline ring show higher selectivity than the monomeric parent CD at ca. one order of magnitude lower concentrations. However, the tandem modifiers linking two or three CD molecules at the 11-position of the quinuclidine moiety are not very effective for the PCA hydrogenation. The enantioselectivity was analyzed from kinetic points of view. It is concluded that the adsorption equilibrium constants of the tandem modifiers are considerably increased by linking CD molecules via the quinoline ring. It is strongly suggested that the CD moieties of these tandem modifiers are synchronized and simultaneously adsorbed on the palladium metal surface together with the intervening aromatic group, resulting in enhanced adsorption strength. In sharp contrast, the tandem modifiers linked with alkyl groups at the 11-position of the quinuclidine moiety behave as independent, free CD molecules in spite of being linked.